The performance and clinical utility of cervical microscopy for the diagnosis of gonorrhoea in women in the era of the NAAT. (August 2015) - Thorley, Nicola; Radcliffe, Keith
We evaluated the performance and clinical utility of cervical microscopy for diagnosing genital gonorrhoea (GC) in women, using the APTIMA Combo 2 dual GC/ Chlamydia trachomatis assay as the gold standard. Test performance was assessed overall and for patient subgroups (symptomatic, GC contacts, pelvic inflammatory disease [PID] diagnosis). It was found that 93 women had positive GC genital NAAT results; 15 had positive cervical microscopy (8 were GC contacts). In all subgroups except GC contacts, the PPV of cervical microscopy was below the nationally accepted target of 90%. Compared to APTIMA Combo 2, cervical microscopy has poor sensitivity for diagnosing GC in women (16.1% overall, 17.3% symptomatic, 25% GC contacts, 10.5% PID). GC contacts accounted for over 50% of the positive microscopy results and would have received epidemiological treatment for GC, regardless of the microscopy result. Discontinuing the routine use of cervical microscopy would improve patient flow through the sexual health clinic and resources could be utilised more effectively.